PENGARUH CAR, LDR, BOPO, NPL DAN SIZE TERHADAP PROFITABILITAS BANK - Efa Wahyu Setiyani, 09.05.52.0123; Sudarsi, Sri (Students Journal of Accounting and Banking, 2013)
The objective of this research is to analyze the effecctt Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Operasional Cost To Operasional Income (BOPO), Non Performing Loan (NPL), and SIZE to theÂ  Profitability (ROA). The population used in this research are all of the visted banking in Indonesian Stock Exchange the period 2008-2011. And form the purpose sampling method and find 20 companies that the criteria. Analysis method used in this research is multiple regression with a significancy level 5%. From the result of the test to the research simultaneous is known thatÂ  CAR. LDR, BOPO, NPL and SIZE significantly affected this profitability (ROA) of banking in BEI with a significancy 0,000. Being of the parsial test result to bank in BEI indicates that the variable LDR and SIZE has positive and significantly to profitability (ROA). Variable CAR, has positive and no significantly effect on profitability (ROA) of Bank. While the BOPO, NPL has negative and significantly to profitability (ROA). Keywords: ROA, CAR, LDR, BOPO, NPL, SIZE .